Double obstacle phase field approach to an inverse problem for a discontinuous diffusion coefficient. (16th March 2016) - Deckelnick, Klaus; Elliott, Charles M; Styles, Vanessa
Abstract: We propose a double obstacle phase field approach to the recovery of piece-wise constant diffusion coefficients for elliptic partial differential equations. The approach to this inverse problem is that of optimal control in which we have a quadratic fidelity term to which we add a perimeter regularization weighted by a parameter σ . This yields a functional which is optimized over a set of diffusion coefficients subject to a state equation which is the underlying elliptic PDE. In order to derive a problem which is amenable to computation the perimeter functional is relaxed using a gradient energy functional together with an obstacle potential in which there is an interface parameter ϵ . This phase field approach is justified by proving convergence to the functional with perimeter regularization as . The computational approach is based on a finite element approximation. This discretization is shown to converge in an appropriate way to the solution of the phase field problem. We derive an iterative method which is shown to yield an energy decreasing sequence converging to a discrete critical point. The efficacy of the approach is illustrated with numerical experiments.